Alternate Reality Game and Augmented Reality: Do They Complement in Promoting Students' Self-Efficacy for Science Learning - Indayati, Tatik; Rahayu, Wulan; Karinsa, Hanah (Jurnal Pendidikan MIPA, 2024)
Self Efficacy (SE) plays an important role in improving students' academic achievement in science education. This study explores the integration of Alternate Reality Games (ARG) and Augmented Reality (AR) technology to improve students' SE during science learning. Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, this research analyzes 41 studies published between 2020 and 2024. The PICO methodology was applied: Participants (students in science education), Intervention (ARG and AR implementation), Comparison (traditional teaching methods), and Outcome (improved SE). ARG immerses students in interactive narratives and problem-solving scenarios, fostering critical thinking and resilience, while AR enhances conceptual understanding through immersive and visual simulations of scientific phenomena. The combined ARG and AR app offers a comprehensive learning experience, facilitating deeper engagement and increased confidence in academic abilities. However, challenges such as technological infrastructure and educator readiness remain significant barriers to implementation in developing countries. These findings highlight the complementary roles of ARG and AR in advancing science education, demonstrating their potential to create inclusive and engaging learning environments. However, AR plays a more significant role than ARG, particularly in enhancing students' conceptual understanding and active participation, which directly impacts their self-efficacy.        Keywords: self efficacy, alternate reality games, augmented reality.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1329-1346